The Perspective of Quranic Interpretation of Surah An-Nisa on Inheritance Practices in Indonesia - Tampubolon, Arsyaf; Tarigan, Azhari Akmal; Syahriza, Rahmi (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study explores the Quranic interpretation of Surah An-Nisa, verses 11 and 12, regarding inheritance practices in Indonesia, focusing on justice and gender equality. These verses set rules for inheritance distribution that differentiate male and female heirs, aiming for a balance of rights and responsibilities. However, customary laws in some Indonesian communities often conflict with these rules, hindering women's inheritance rights and causing tension between local customs and Islamic principles. Using a qualitative, library-based approach, this study analyzes how understanding these verses can promote fair and equitable inheritance laws, fostering a more inclusive and socially responsive system in the modern era.